ON MATHEMATICAL MODELS OF THE ALLER EQUATION - Khubiev K. U. (Vestnik KRAUNC: Fiziko-Matematičeskie Nauki, 2016)
The solution to the Goursat problem is written out explicitly for a hyperbolic secondorder loaded equation, proposed as a mathematical model of Aller equation under certain conditions.